The stylistics of external music in Yahya Ibn Hakam Al-Ghazal’s Divan . - Yekhlef, Assia (Journal of Human Sciences, 2022)
This study attempts to acces some of the characteristics of Andalusian thought by studying the characteristics of external music in the poetry of the Andalusian poet Yahya Ibn Hakam , Nicknimed Al Ghazal . We tried to show that through his poetry compiled by Mohamed Radwan Al Daya. In this research , we used the descriptive approach and the statistical process . Music is closely lincked to the content of the text we can reveal the aesthetics and artistic secrets of this text through its music . It enables us to explore the elements of style and to define their internal relationships that have made it a coherent and a cohesive structure .